Paciente masculino de 76 años de edad con tumor maligno en la laringe - Segura Riera, Lady Johanna (2021)
In this clinical case study, a 76-year-old patient with information about discomfort and pain in the tracheostom is shown as a reference, a laryngoscopy is performed, which gives rise to a tracheostomy and a gastrostomy is planned, the patient maintained a hospitalization record, where the passage of time was given a diagnosis of a malignant tumor in the larynx. Specialist doctor orders a series of examinations to perform a gastrostomy intervention for the patient and improve their nutritional compensation, the examinations to be performed were hematic biometry, biochemicals and blood coagulation, he also performed a physical examination where he showed moist mucous membranes, neck, cervical region with Functional, cardiorespiratory tracheostomy with audible gallbladder murmur with swelling rales of cardiovascular unfolding without alterations, abdomen surgical wound without bruising without secretions pathologies with patent gastrostomy tube, soft depressible slightly painful on deep palpation in the surgical area without peritoneal reaction noises present, extremities symmetrical, no edema. Patient is sent for consultation where the nutritionist for an adequate nutritional assessment and nutritional counseling for the enteral route that he presents, nutritionist sends the patient with a broad liquid hyperprotein diet to maintain the patient's nutritional status in an adequate way since his body mass index he finds himself with a normal diagnosis, despite receiving an inadequate diet for the nutritional requirement that the patient needs. Nutritional follow-up is carried out to incorporate diet by enteral route, by gastric tube, the patient in the first months registers a weight loss of 2 kilograms and a recovery with diet coupling according to his needs of 0.5 kilograms.